Identification, localization and knock-out of pyrenoid components in the diatom Phaeodactylum tricornutum - Ng, Yi Siang (Nanyang Technological University, 2025)
Ribulose-1,5-bisphosphate carboxylase-oxygenase (Rubisco) is the enzyme responsible for most photosynthetic carbon dioxide fixation. Surprisingly, it is an inaccurate and slow catalyst, occasionally reacting with O2 instead of CO2 to create wasteful byproducts. To minimize Rubisco’s shortcomings, photosynthetic organisms have evolved carbon dioxide concentrating mechanisms (CCMs) that increase the local concentration of CO2 around Rubisco. This enhances carboxylation velocity and reduces oxygenase activity. Most photosynthetic algae perform this by isolating Rubisco in a membrane-less compartment, called the pyrenoid, which is then supplied with CO2 via active transport of bicarbonate. The model diatom Phaeodactylum tricornutum contains a poorly characterized pyrenoid. Pyrenoid Component 1 (PYCO1), an intrinsically disordered repeat protein, was recently identified and was shown to undergo liquid-liquid phase separation in vitro to form condensates that can specifically recruit P. tricornutum Rubisco. This study aimed to investigate the physiological function of PYCO1 by ablation using CRISPR/Cas9 gene editing. Bi-allelic genome edited strains were isolated, and both immunoblotting and mass spectroscopy supported the loss of PYCO1 in the edited strain. Surprisingly, TEM imaging of the edited strain did not reveal noticeable changes in pyrenoid ultrastructure versus wild type, and O2 electrode measurements detected only a small reduction in photosynthetic performance, indicating that additional protein players that are involved in the pyrenoid structure are yet to be identified. Multiple additional pyrenoid candidate proteins were identified due to the presence of multiple Rubisco binding motifs. 6 pyrenoid candidate proteins were localised using fluorescent protein tagging, revealing distinct localisation behaviours that suggests specific roles in pyrenoid function and/or formation. Our findings expand the knowledge on pyrenoid composition in diatoms and inform future engineering efforts in expressing pyrenoids in higher plant species.